7th International symposium on health informatics and bioinformatics - Ahmad, Rashidi (Universiti Sains Malaysia, 2012)
ULTRASONOGRAPHIC ABDOMINAL AORTA DIAMETER CHANGES: A PREDICTOR OF HYPOVOLEMIC SHOCK CLASS 1